Sustainable Mining Management in Afghanistan: Challenges and Solution - Nero, Mohammad Arif (Journal of Natural Sciences – Kabul University, 2025)
Afghanistan is richly endowed with mineral resources. At present, these contribute little to the economy or the society. A large mining activity in Afghanistan is illegal, but also mining in the country faces numerous challenges. The main objective of this review is to examine the challenges and propose appropriate strategies for the optimal utilization of the country’s mineral resources. The information has been collected from scientific sources and reliable databases. The findings of this study indicate that the lack of regulations frameworks, limited technical expertise, uncertainty regarding mineral resources, neglect of environmental, social, and economic impacts of mining, and the severe lack of infrastructure are among the key challenges to sustainable mineral extraction. Mining in Afghanistan requires the clarification of laws and regulations, full contracts and revenues, prioritization of local employment opportunities, attention to environmental, economic, and social issues, utilization of modern technology, implementation of exploration activities by the government, increased incentives, and training of specialized personnel.